Immune Check Point Inhibitors and Immune-Related Adverse Events in Small Cell Lung Cancer - Hou, Wanting; Zhou, Xiaohan; Yi, Cheng; Zhu, Hong (Frontiers in Oncology, 2021)
Small cell lung cancer (SCLC) is a malignant solid tumor. In recent years, immune check point inhibitors (ICIs) have achieved important advances in the treatment of SCLC, while immune-related adverse events (irAEs) have also been reported during the therapeutic period. Some irAEs lead to dose reduction or treatment rejection. The immune microenvironment of SCLC is complex. Understanding the irAEs of ICIs is of significant importance for the clinical management of SCLC. But a comprehensive understanding of irAEs in SCLC patients is still lacking. This review aims to provide an up-to-date overview of ICIs and their associated irAEs in patients with SCLC based on the existing clinical data.